An innovative design of a high strength and low weight sudden micro expansion by considering a nanofluid: Electronic cooling application. (December 2021) - Safaei, Mohammad Reza; Abdelghany Elkotb, Mohamed; Alsharif, Abdullah M.; Mansir, Ibrahim B.; Alamri, Sagr; Tirth, Vineet; Goodarzi, Marjan
Abstract: The present study has been numerically surveyed the effect of different expansion angles on the heat transfer and pressure drop characteristics of a sudden expansion in a microtube. For this purpose, Cu/water nanofluids flowing with Reynolds numbers (Re) of 10, 25, 50, and 100 through expansion angles of 30°, 45°, 60°, and 90° were modeled. Governing equations were solved by the finite volume method (FVM). The findings indicated that the heat transfer coefficient (HTC) could enhance by nanoparticles concentration and Re augmentation. Also, It was revealed that HTC of a sudden expansion with an angle of 45° has optimum hydrodynamic performance; then, sudden expansions of 30°, 90°, and 60° are followed. The highest HTC was achieved for a microtube containing 4 vol% nanofluids at Re = 100 with a 45° expansion angle, 43.63% higher than conventional expansion angle (90°) working with distilled water at Re = 10. By comparing HTC at various angles, it can be found that there is a 14.57% further HTC by changing the expansion angle from α = 90° with α = 45°. Furthermore, the pressure drop investigation showed that the expansion angle with α = 30° has the lowest pressure drop. In contrast, α = 45° produced the highest pressure drop because of giant vortices created along the tube wall. The velocity streamlines and contours explained the reason for a lower pressure drop of α = 30°, 45°, and 60° which was regular streamlines along the tube wall due to the Coanda effect.